Information technology for governance and efficiency - Pardhasaradhi, Y. (2004)
The article introduces the concept of efficiency in the changing definitions and understanding of the public administration from Wilsonian period to the 21st Century with analysis of different concepts and dimensions of governance and the transforming role of state. Use of technology in government has changed the organisational structure and created different human and organisational networks based on electronic and automated systems. It explains different problems and areas of concerns which need to be given due consideration for implementing ICT in government for an efficient governance. - Reproduced.
Keywords: Good governance; E governance; Information technology